2004
DOI: 10.1021/la0356396
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Metal Colloid Films:  Two Approaches for Preparing New SERS Active Substrates

Abstract: In this paper, we propose two new approaches for preparing active substrates for surface-enhanced Raman scattering (SERS). In the first approach (method 1), one transfers AgI nanoparticles capped by negatively charged mercaptoacetic acid from a AgI colloid solution onto a quartz slide and then deoxidizes AgI to Ag nanoparticles on the substrate. The second approach (method 2) deoxidizes AgI to Ag nanoparticles in a colloid solution and then transfers the Ag nanoparticles capped by negatively charged mercaptoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 60 publications
6
103
1
Order By: Relevance
“…28 Briefly, clean quartz slides were immersed in 0.5% PDDA solution for about 30 min and then rinsed with triply distilled water. The slides were immersed in the AgI colloid for about 20 min and then rinsed with triply distilled water.…”
Section: Sers Substrate Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Briefly, clean quartz slides were immersed in 0.5% PDDA solution for about 30 min and then rinsed with triply distilled water. The slides were immersed in the AgI colloid for about 20 min and then rinsed with triply distilled water.…”
Section: Sers Substrate Preparationmentioning
confidence: 99%
“…This problem can be largely overcome by transferring the metal nanoparticles on to a solid substrate. In our previous studies, 28 we reported an in situ reduction method to prepare SERS substrates, in which AgI nanoparticles are transferred from the colloid and then reduced to Ag nanoparticles on the solid substrate. The SERS substrate thus obtained exhibited strong enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…These active films should also be stable, reproducibly prepared, inexpensive, and easy to make. [22][23][24][25] In reali-…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, many approaches were proposed to optimize and control the surface-enhanced Raman scattering efficiency of colloidal AuNPs assembled on substrates into 2D nanostructures [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%